Tindak Tutur dalam Iklan Lebaran Mr.Diy 2022 “Kembali Ke Pangkuan” - Wibisono Yudhi Kurniawan (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2023)
Advertising is one of the strategies employed by producers to promote their products or services. The purpose of this research is to analyze the discourse in the MR.DIY 2022 Eid advertisement